Comparison of Osteoporosis in Two Different Regions of Turkey - Umut Hatay Gölge; Erkam Kömürcü; Burak Kaymaz; Ferdi Göksel; Yunus Güzel; Gürhan Adam; Pırıl Erbay (Türk Osteoporoz Dergisi)
Objective: The aim of the study was to investigate the effect of different climate and geographic conditions on bone mineral density. Materials and Methods: The patients who had been examined with Dual X-ray Absorptiometry (DXA) for the suspicion of osteoporosis in two different regions of Turkey were included in the study. Medical records of these 2457 patients were evaluated retrospectively. Age, gender, body mass index (BMI) and osteoporosis etiology of these patients were recorded. Results: Dual X-ray Absorptiometry measurements of the femoral neck and lomber vertebras of these patients were investigated. 927 of the patients were found to be osteoporotic and 907 of the patients to be osteopenic. There was no difference between the groups in terms of age, gender and BMI. Lumbar vertebras (L1-4) and femoral neck T scores of the patients with similar age and gender in these 2 different regions were compared and the difference between the groups was found to be statistically significant (p<0.001). Conclusion: The effect of geography and climate conditions on the bone quality is well known. In this respect regional strategies in the prevention and treatment of the osteoporosis may be judicious. (Turkish Journal of Osteoporosis 2014;20: 56-9)